EMPOWERMENT OF DAIRY CATTLE FARMERS IN THE AREAS SELINGKAR WILIS THROUGH COMMUNITY SERVICE’S POSTGRADUATE SCHOOL: PEMBERDAYAAN PETERNAK SAPI PERAH DI SELINGKAR WILIS, PENGABDIAN KEPADA MASYARAKAT SEKOLAH PASCASARJANA - Yuliani, M. Gandul Atik; Madyawati, Sri Pantja; Hariyono, Hariyono (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: The Postgraduate School strives to establish itself as a world-class institution with a significant global impact. To achieve this vision, it has forged partnerships with regional leaders, emphasizing community service. Our latest initiative, "Community Empowerment of Dairy Cattle Breeders in Selingkar Wilis, Trenggalek Regency," aligns with the Sustainable Development Goals (SDGs). Objective: This initiative aims to empower the community in the Wilis region by providing training in dairy cattle reproduction and production. Method: The program is implemented in two key stages: (1) Offering guidance and training to dairy farmers, and (2) Monitoring and evaluating the outcomes. We measure knowledge gains through assessments conducted before and after the training sessions. Results: Evaluations indicated a significant improvement in dairy farmers' understanding of reproductive health management and the control of Foot and Mouth Disease in their cattle. Conclusion: This initiative has successfully enhanced the skills of breeders in the Wilis area, equipping them to address reproductive issues and manage Foot and Mouth Disease, thereby supporting the agricultural community in Trenggalek Regency.